Olhar sobre capacitação: conhecimento elaborado pelas enfermeiras do programa de saúde da família - Vilela, Alba Benemérita Alves (2003)
Due to the approach systematic and to obtained data analysis, this thesis work may be recognized by its qualiíative nature on the basis of Social Representations Theory (TRS) of Sergí Moscovici. The naain goals were to apprehend social represeníations in the practice of college levei nurses qualified by Bahia’s Family Health Program Personnel Capacitating and Permanent Education Pole, and what determinate those represeníations; to comprehend the construetion of those represeníations by college levei professionals involved in the program; to study the importance of the represeníations elaborated by college levei nurses, relatively to dimensioning their practice in the program; and to describe the contribution of social representations in the evaluation of professional practice of college levei nurses qualified by the Pole. The methodological path was, first, to list social actors that focused in this work: male and female nurses graduated by two specializing courses of the Pole, from 1996 to 1999, in Jequié campus of Southern Bahia State University; then, in connection with health secretaries of each municípality, to ask the graní of their municipal health councils to iníerview and observe, in their work fiekl, those nurses activities, scheduling interviews in their work places. Semi-structured iníerview, fiekl observation registered in fiekl log and free word association were used for data construction. Free word association was analyzed through Tri-deux Mot software. Bardin (1977) and Vala' (1999) content analysis was used for iníerview categorization, considering that their theories match the lines of this work. That analysis was based on three poínts — Tri-deux software, iníerview content analysis and field log for that method fit TRS. In conclusion, it was understood that, for nurses with less than five years Service and under 30, the specializing courses were apprehended and represented as an apprenticeship that lead to a change in their daily practice;'meanwhile, nurses with more than five years Service and over .^0 represented those courses as apprenticeship. It was validated by final content analysis. thht the nurses speech showed observations on a significam change in their trajectory through new ways of seeing^istening, reflecting, evaluating and action planning, in PACS and PSF teams of the municipalities where they work. It was pointed that PACS and PFS nurses’ profile was constructed within realizations and actions from the path of their activities in those programs. There is alsodhe comprehension that those courses meet, in some way, the demands of the social actors focused in this work, but need to be refined irqorder to fill the lacks always neglected in the process of health professionals permanent educàtion, which is nothing more than widely and permanently taking care of another one.